SEM analysis of the in situ early bacterial colonization on two novel feldspathic ceramics submitted to different types of glazing - Pereira, Sarina Maciel Braga [UNESP]; Kantorski, Karla Zanini; Brentel, Aline Scalone [UNESP]; Valandro, Luiz Felipe [UNESP]; Bottino, Marco Antonio [UNESP] (My University, 2008)
Aim: The aim of this study was to evaluate in situ, the early bacterial colonization on feldspar-ceramics submitted to different glazing. Methods and Materials: Fourteen standardized disc specimens (diameter: 5 mm, thickness: 1.5 mm) of each of two micro-particulate feldspathic ceramics (VM7 and VM13, Vita) were produced according to manufacturers' specifications for a total of 28 specimens (24 for the analysis of biofilm and 4 for topographic analysis analyzing the ceramic surfaces). Specimens from each type of ceramic were submitted to two different glazing methods composing four groups: VM7 glazed using glazing liquid Vita Akzent® 25 (G1) and glaze firing (G2), VM13 glazed using glazing liquid (G3) and glaze firing (G4). Six individuals (n=6) wore oral appliances with four ceramic specimens, fixed on the buccal face of the appliances. After 8 hours, each sample was evaluated for the presence (1) or absence (0) of bacterial colonization under a scanning electron microscope (SEM) on five randomly selected fields. The value for each sample was cumulative of the results observed in the fields. One sample from each group was evaluated under a SEM to verify the topographic pattern. Results: There was no difference with regard to bacterial colonization between the feldspar-ceramics and between the glazing types (Kruskal-Wallis non-parametric test). Conclusion: Feldspar-ceramics submitted to firing or glaze firing with Vita Akzent® 25 present a similar condition for in situ bacterial colonization. The similar topographic pattern of the ceramic surfaces seems to have influenced the bacterial colonization.
Keywords: Acquired pellicle; Bacterial colonization; Feldspathic ceramic; Glazing; Microscopic analysis; aluminum silicate; potassium derivative; bacterial count; biofilm; denture; feldspar; human; microbiology; nonparametric test; scanning electron microscopy; surface property; tooth prosthesis; Aluminum Silicates; Biofilms; Colony Count, Microbial; Dental Porcelain; Dental Veneers; Denture, Partial; Humans; Microscopy, Electron, Scanning; Potassium Compounds; Statistics, Nonparametric; Surface Properties